Pengembangan Model Alat Ajar Ilmu Pengembangan Materi Daur Ulang Sirkuit Darah Manusia Untuk Siswa Kelas V Sd Negeri 16 Toboali - Suciva Triabela; Erika Fitri Wardani; Fandi Nugroho (JBES (Journal Basic Education Skills), 2023)
This research is motivated by the availability of learning media which is still limited and based on an analysis of students’s needs that media is needed in the learning process. The aim of this research is to develop a science teaching aid with a cross-sectional model of human blood circulation made from recycled material that is feasible and practical for fifth grade elementary school students. This type of research uses research and development (R&D) with the ADDIE procedure with 5 stages, such as analysis, design, development, implementation, and evaluation. The subjects in this study were fifth grade students at SD Negeri 16 Toboali. Data collection techniques and instruments in the form of a questionnaires. The data analysis technique is in the form of quantitative descriptive, namely the feasibility data carried out by material experts and media experts using a questionnaire with a Likert scale. Practicality data is carried out thought teacher responses and students responses using the Guttmen scale. Based on the results of the material validator’s assessment, it was found to be 95,3% (very eligible) and the media validator was 81,8% (very eligible). The practicality test results are known to be 83,8% (very practical). The result of the teacher’s response through a questionnaire was 100% (very practical). Therefore, it can be interpreted that the learning media for science teaching aid, a Cross-Sectional Model of Human Blood Circulation Made from Recycled Materials in fifht grade in Elementary School Students, is very feasible and practical to use